DC/AC conversion efficiency of grid-connected photovoltaic inverters in central Mexico. (1st December 2016) - Rodrigo, P.M.; Velázquez, Ramiro; Fernández, Eduardo F.
Highlights: DC/AC efficiency of grid-connected photovoltaic inverters at central México. The influence of DC input voltage is considered. Crystalline silicon and Cadmium Telluride photovoltaic modules are investigated. Maximum losses due to a suboptimal string configuration are 1.3% of annual efficiency. Array-to-inverter sizing ratio of 1.05 for c-Si and 0.95 for CdTe is recommended. Abstract: The DC/AC conversion efficiency of grid-connected photovoltaic inverters depends on climatic characteristics, technical characteristics of the inverters and PV modules, array orientation, ratio of array peak power to inverter nominal power and DC input voltage fed to the inverter. The influence of the DC input voltage in DC/AC conversion efficiency was investigated by Zhu et al. (2011) for a high-latitude maritime climate. In this paper, all the aforementioned factors, including the DC input voltage, are analyzed for the case of the low-latitude semi-desert climate of Aguascalientes, central México. Solar irradiance and temperature measurements of 10 years are used to generate a year of typical characteristics which is the basis of the research. Two commercial grid-connected photovoltaic inverters with different efficiency behavior with respect to DC input voltage and PV technologies based on crystalline silicon and Cadmium Telluride are characterized. The research reveals that maximum losses in annual inverter efficiency due to a sub-optimal string configuration are 1.3% for the analyzed technologies. Rules for sizing the array voltage and array power which keep high annual inverter efficiency while reducing the balance-of-systems costs are recommended. For optimally oriented systems, the recommended array-to-inverter power sizing ratio is 1.05 for c-Si and 0.95 for CdTe independently of the chosen inverter at central México. The methodology can be replicated to other locations, inverters and photovoltaic technologies.